2022
DOI: 10.1558/jcsr.22389
|View full text |Cite
|
Sign up to set email alerts
|

Rituals, Music, and the Landscape Metaphor

Abstract: In this commentary, we discuss two aspects of The Ritual Animal’s (2021) rich and multidimensional framework which may be further developed: the role of music and euphoric rituals within Harvey Whitehouse’s modes theory, and the use of the landscape model for studying sociocultural systems. We note the strong, cross-cultural association of music and religious rituals, consider the suitability of music for such practices, and suggest further research on how the use of music may accommodate both imagistic and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…We need, however, to do more than translate the terms of Waddington's embryological landscape metaphor into the terms of social science. As we emphasized (Tavory et al, 2012Shilton & Jablonka, 2022), when translating and applying the metaphor to the social-cultural domain, we assume the following:…”
Section: Interacting Network In Social Landscapesmentioning
confidence: 99%
See 2 more Smart Citations
“…We need, however, to do more than translate the terms of Waddington's embryological landscape metaphor into the terms of social science. As we emphasized (Tavory et al, 2012Shilton & Jablonka, 2022), when translating and applying the metaphor to the social-cultural domain, we assume the following:…”
Section: Interacting Network In Social Landscapesmentioning
confidence: 99%
“…Following such transient bursts, orthodoxy is re-established and reaffirmed. Whitehouse suggested that employing the landscape metaphor suggested by Tavory et al (2012 and applying a multilevel landscape analysis that includes epigenetic, cognitive-developmental, and social-historical landscapes may elucidate the dynamics of social systems (for a discussion of this suggestion, see Shilton & Jablonka, 2022).…”
Section: The Stability Of Mainstream Kivung Religious Practices Punct...mentioning
confidence: 99%
See 1 more Smart Citation